2016
DOI: 10.1097/md.0000000000003767
|View full text |Cite|
|
Sign up to set email alerts
|

Dickkopf-1 negatively regulates the expression of osteoprotegerin, a key osteoclastogenesis inhibitor, by sequestering Lrp6 in primary and metastatic lytic bone lesions

Abstract: Recently, an inverse role for Wnt signaling in the development of osteoclasts in the bone was demonstrated. In the present study, we examined whether there is a commonality in the mechanism of bone resorption and lysis that occur in a diverse set of bone metastatic lesions, as well as in primary bone lesions. Compared with control bone tissue and bone biopsies from patients with nonmetastatic primary tumors (i.e., breast carcinoma, lung adenocarcinoma, and prostate carcinoma), patients with bone metastatic les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
(20 reference statements)
0
4
0
1
Order By: Relevance
“…In addition to this, a further study found an over-expression of Dkk1 in bone biopsies of lytic lesions from patients with multiple myeloma and metastatic cancers when compared with bone biopsies of patients with primary cancers only. This expression correlated with a decrease in the level of OPG; further increasing the activation of osteoclasts, and so generating a heightened level of bone destruction [11].…”
Section: Introductionmentioning
confidence: 89%
“…In addition to this, a further study found an over-expression of Dkk1 in bone biopsies of lytic lesions from patients with multiple myeloma and metastatic cancers when compared with bone biopsies of patients with primary cancers only. This expression correlated with a decrease in the level of OPG; further increasing the activation of osteoclasts, and so generating a heightened level of bone destruction [11].…”
Section: Introductionmentioning
confidence: 89%
“…В биоптатах, полученных из очагов остеолизиса у пациентов с ММ и метастатическими солидными опухолями, была обнаружена гиперэкспрессия Dkk1. Степень экспрессии этого белка коррелировала со снижением концентрации OPG, активацией остеокластов и степенью остеодеструкции [16].…”
Section: поддерживающая терапияunclassified
“…In the presence of sclerostin, DKK-1 decreases β-catenin, which reduces differentiation of osteoblasts. (37,110) A humanized immunoglobulin G (IgG) anti-DKK-1 monoclonal antibody, BHQ880, has been evaluated in vitro and in vivo. (111) BHQ880 was successful at reversing the inhibiting effect of DKK-1 on osteoblast differentiation and promoted bone formation in a murine model of human MM.…”
Section: Anti-dkk-1mentioning
confidence: 99%